P113 The cost-effectiveness of step down from high dose fluticasone/salmeterol dry powder or suspension formulations in asthma applied to the UK setting. (2nd December 2011) - Paggiaro, P L; Buseghin, G; Nicolini, G; Patel, S; Iannazzo, S; Zaniolo, O; Papi, A
Abstract : Objectives: The stepwise management of asthma outlined in the BTS/SIGN guideline recommends stepping down asthma patients where control is achieved. The aim of this analysis was to estimate the costs and health outcomes associated with step down of controlled patients on high dose fluticasone/salmeterol (FP/S 1000/100 μg daily) to either extrafine beclometasone/formoterol (BDP/F 400/24 μg) pMDI or medium dose FP/S (500/100 μg) dry powder in the UK setting. Methods: A patient-level simulation Markov model was constructed to enable the simulation of a cohort of patients through three comparative arms (FP/S 1000/100, FP/S 500/100, BDP/F 400/24). Transition probabilities and healthcare resources costs were derived from a recent multinational clinical trial comparing BDP/F 400/24 μg vs FP/S 500/100 μg as step down therapy in asthma. Direct costs and health state utilities were sourced from UK costs and published literature. The cost of FP/S 1000/100 was calculated considering the dry powder formulation. An additional analysis was conducted considering the suspension formulation. The analysis was conducted from a UK health system perspective, based on 6 months horizon. Probabilistic sensitivity analyses were conducted. Results: The analysis showed that there was an ICER (Incremental Cost-Effectiveness Ratio) of 32 000 GBP/QALY (Quality Adjusted Life Years) associated with high dose dry powder FP/S 1000/100 μg vs extrafine BDP/F 400/24 μg and an ICER of approximately 36 800 GBP/QALY associated with medium dose dry powder FP/S 500/100 μg vs BDP/F 400/24 μg. Additional analysis showed that there was an ICER of 85 200 GBP/QALY associated with high dose suspension formulation FP/S 1000/100 μg vs extrafine BDP/F 400/24 μg. Conclusions: BTS/SIGN guideline recommend that when asthma control is achieved, treatment can be stepped down to the lowest dose that maintains control. It was found that maintaining controlled patients on high dose FP/S is not cost-effective. Extrafine BDP/F 400/24 μg daily can be considered to be a cost-effective option in the UK to maintain control of asthmatic patients stepped down from high dose FP/S 1000/100 μg daily dry powder or suspension formulations and the magnitude of cost effectiveness is estimated to be highest when stepping down from the suspension formulation.